(untitled) (Third Sector Social Economic Review, 2021)
Nowadays, where internet technologies are used extensively, still there are too many companies not to be involved in digital marketing. But digital marketing is evolving and diversifying day by day. Thus, there are differences between digital marketing activities of companies. In this respect, this research has two purposes. These purposes are; firstly, to determine the current digital marketing activities, and secondly, classified the determined digital marketing activities as beginner, intermediate and advanced level. In order to achieve these goals, the research has been planned in two stages. In the first stage; In order to determine digital marketing activities, data were collected from 32 academicians who are experts in the field of digital marketing via open-ended questionnaire. In the second stage; classified the according digital marketing activities as beginner, intermediate and advanced levels, data were collected from 64 academicians who are experts in digital marketing via structured questionnaire. As a result of the research; 122 digital marketing activities were identified and classified into 12 beginner level, 43 intermediate level and 67 advanced level.